Cardiovascular Acute Effects of Traditional vs. Paired Set Resistance Training in Patients With Liver Cirrhosis. Issue 4 (1st October 2020) - Nasser, Igor; Perez, Renata de Mello; Reis, Michel Silva; Dias, Ingrid; Willardson, Jeffrey M.; Miranda, Humberto
ABSTRACT: Purpose : This study compared the acute effects of two different resistance training methods on heart rate variability, blood pressure, and rating of perceived exertion in patients with liver cirrhosis. Methods : Ten patients with Child-Pugh A (seven women and three men) participated in two experimental sessions, in random order: The traditional set condition consisted of three sets of six exercises performed in a sequential manner, while the paired set condition consisted of alternating sets between two exercises (three pairs of exercises). Ten repetitions were performed for each set with 70% of a 10 repetition maximum load and with 2 min rest between sets. Blood pressure and heart rate variability were assessed pre-workout and for 60 min post-workout. The rating of perceived exertion was assessed at the end of the third set for each exercise. Results : Significant alterations in heart rate variability were observed when considering the lowest value obtained during recovery, in which the SDNN was reduced in both the traditional set and paired set conditions, as well as the root mean square of standard deviation for the traditional set condition ( p < .05). Additionally, for the paired set condition, there was a significant reduction in the HFnu band and a significant increase in the LFnu band ( p < .05). Effect size showed reductions in diastolic and mean blood pressure until 30 min in a small magnitude for traditional sets. Conclusion : Similar cardiovascular responses were observed between methods eliciting normal physiological responses within safe limits for patients with liver cirrhosis.